2017
DOI: 10.24051/eee/76920
|View full text |Cite
|
Sign up to set email alerts
|

Tree Diversity and Management of Village Common Forests in Bandarban

Abstract: Village Common Forests (VCF) are used sustainably for water source conservation, livelihoods and other biomass needs ofethnic communities in the hilly areas of Bangladesh. The current forest degradation rate warrants the importance and potentiality of VCF for sustainable natural resources management. This study was conducted in two VCF of Lama and RumaUpazila at Chimbuk hill range in Bandarban district to explore the indigenous management techniques and tree species diversity. To identify tree species diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
(9 reference statements)
1
5
0
Order By: Relevance
“…However, some NGOs have initiated programs to develop the VCF territory and at the same time enhance the livelihood facilities of the community people in order to reduce their dependence on forests as there is no government initiative to protect these forests. Other studies [6,14,36,37] have reported similar findings. In addition, regular meetings with proper goals and management aspects including different initiatives help the communities to manage VCF in a sustainable way.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…However, some NGOs have initiated programs to develop the VCF territory and at the same time enhance the livelihood facilities of the community people in order to reduce their dependence on forests as there is no government initiative to protect these forests. Other studies [6,14,36,37] have reported similar findings. In addition, regular meetings with proper goals and management aspects including different initiatives help the communities to manage VCF in a sustainable way.…”
Section: Discussionsupporting
confidence: 76%
“…The Chittagong hill tracts (CHTs) of Bangladesh covers about 13,294 km 2 combining three hilly districts covering more than 75% is considered suitable for forest resources [6,7]. In CHTs, Village Common Forest (VCF) is a natural forest other than the government forest around the households of the ethnic communities and managed for water source conservation, livelihoods and other biomass needs in the hilly areas of Bangladesh [1,6]. However, the long term sustainability of the VCFs will depend upon how well the local community peoples feel VCF's usefulness in their everyday lives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rangamati district is the Southeastern part of Bangladesh under the Chittagong division, and the topography has a hilly slope and a moderate slope to the valley (Kamrul, Jashimuddin and Hossain, 2017). However, most of the local population, who are Indigenous communities, in the Rangamati district of Bangladesh is also suffering from water scarcity for six years (Miah et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 5,700 species of angiosperms (Mukul, 2007;Rahman and Vacik, 2015), of which about 221 species of plants, have been recorded in BNP (Kabir and Ahmed, 2005). According to BFD, the country has 2.5 million ha of forestland (hill forest, Sal forest and tidal mangrove forest), equivalent to 17.4% of country's total area, out of which 1.6 million ha area is managed by the BFD (BFD, 2016;Islam, Jashimuddin and Hossain, 2017;Rahman and Miah, 2017). Although there are inconsistencies about the total area of forest land, but the National Forest Assessment 2007 reported about 1.44 million ha which is about 9.8% of the total land (MoEF and FAO, 2007).…”
Section: Introductionmentioning
confidence: 99%